Understanding seismic anisotropy in the Rotondo granite: investigating stress as a potential source - K. Behnen; M. Hertrich; H. Maurer; A. Shakas; K. Bröker; C. Epiney; M. Blanch Jover; D. Giardini (Solid Earth)
The hypothesis of stress-induced seismic anisotropy was tested in the Bedretto Lab, a deep underground rock laboratory in the Swiss Alps. Several comprehensive cross-hole seismic surveys were acquired to analyze the directional dependency of seismic-wave velocities in the undisturbed host rock. This requires precise knowledge on the source and receiver positions as well as good data quality that allows the determination of travel times for different wave types. A tilted transverse isotropic (TTI) model that explains the measured data to a first-order approximation can be established. All relevant model parameters are well constrained using P- and S-wave arrival times. However, a systematic misfit distribution indicates that a more complex anisotropy model might be required to fully explain the measurements. This is consistent with our hypothesis that seismic anisotropy has a significant stress-induced component. More controlled laboratory experiments on the centimeter to decimeter scale were performed to validate our field measurements. These measurements show a comparable order of P- and S-wave anisotropy in the rock volume. The knowledge on the driving mechanism for anisotropy in igneous rocks can potentially help to enhance the monitoring of stress field variations during geothermal operations, thereby improving hazard assessment protocols.